Chromosomal divergence and evolutionary inferences in Rhodniini based on the chromosomal location of ribosomal genes (2013)
ABSTRACT: In this study, we used fluorescence in situ hybridisation to determine the chromosomal location of 45S rDNA clusters in 10 species of the tribe Rhodniini (Hemiptera: Reduviidae: Triatominae). The results showed striking inter and intraspecific variability, with the location of the rDNA clusters restricted to sex chromosomes with two patterns: either on one (X chromosome) or both sex chromosomes (X and Y chromosomes). This variation occurs within a genus that has an unchanging diploid chromosome number (2n = 22, including 20 autosomes and 2 sex chromosomes) and a similar chromosome size and genomic DNA content, reflecting a genome dynamic not revealed by these chromosome traits. The rDNA variation in closely related species and the intraspecific polymorphism in Rhodnius ecuadoriensis suggested that the chromosomal position of rDNA clusters might be a useful marker to identify recently diverged species or populations. We discuss the ancestral position of ribosomal genes in the tribe Rhodniini and the possible mechanisms involved in the variation of the rDNA clusters, including the loss of rDNA loci on the Y chromosome, transposition and ectopic pairing. The last two processes involve chromosomal exchanges between both sex chromosomes, in contrast to the widely accepted idea that the achiasmatic sex chromosomes of Heteroptera do not interchange sequences.